Pemetaan Zonasi Kerawanan Bencana Gerakan Massa Tanah di Kabupaten Puncak, Provinsi Papua - Prabawa, Bayu Argadyanto; Febriarta, Erik; Ardiyanto, Ridwan; Rosaji, Fredi Satya Candra (Universitas Negeri Yogyakarta, 2023)
The geographical and geomorphological conditions of Puncak Regency has a probability of experiencing the disaster, and based on news, it was found that the mass movements had occurred in Puncak Regency and claimed lives. This research aims to map the mass movement susceptibility zonation in Puncak Regency and analyze the factors that influence it. Method used in this research is a statistical model Frequency Ratio using several variables such as slope, aspect, rock type, lineament density, distance from geological structures, soil texture, distance from rivers, and distance from roads. The model results validated using the Area Under Curve value. The results shows that Puncak Regency dominated by the non-susceptible to moderately susceptible in the northern part, while the Puncak Jaya mountains has a high-very high susceptibility class. The most influential variables on the occurrence of mass movement are rock type, lineament density, and slope. The validation results show that the results of the mass movement susceptibility model is statistically acceptable.